Non-aqueous electrolyte and lithium battery
By using a specific proportion of nonaqueous electrolyte components in lithium-ion batteries, including lithium hexafluorophosphate, lithium difluorosulfonimide, fluorovinyl carbonate and the first additive, the problems of lithium-ion batteries with a large expansion and high impedance in high temperature environments are solved, and better circulation performance and fast charging capabilities are achieved.
Patent Information
- Application Number
- CN202411624722.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-18
AI Technical Summary
Existing lithium-ion batteries have problems such as high expansion and high impedance in high temperature environments, and it is difficult to take into account the needs of fast charging.
A non-aqueous electrolyte is adopted, including lithium hexafluorophosphate, lithium difluorosulfonimide, fluorovinyl carbonate and the first additive, and meets a specific mass percentage ratio, and works synergistically to inhibit high-temperature storage of the battery, reduce impedance and improve circulation performance.
Effectively suppress high-temperature storage and gas production of batteries, reduce battery impedance, improve circulation performance, and take into account battery fast charging needs.
Smart Images

Figure CN119650848A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage batteries, and in particular relates to a non-aqueous electrolyte and a lithium battery. Background Art
[0002] At present, the demand for continuous improvement of the energy density of lithium-ion batteries is getting higher and higher. In recent years, increasing the voltage has gradually become one of the mainstream methods to improve the energy density of batteries. By increasing the battery charging cut-off voltage, the positive electrode material can release more lithium ions at a higher voltage, thereby increasing the capacity and working voltage at the same time, thereby achieving the purpose of improving the energy density. However, increasing the charging voltage can easily cause the surface structure of the positive electrode material to be reconstructed, the transition metal to dissolve and deposit on the negative electrode surface, etc., resulting in reduced cycle stability and affecting battery performance.
[0003] In existing lithium-ion batteries, fluoroethylene carbonate (FEC) is considered to be one of the key additives to effectively improve the cycle performance of lithium-ion batteries, but a high content of fluoroethylene carbonate will aggravate the problem of gas production during high-temperature storage of batteries. Therefore, the existing solution needs to control the amount of FEC added. For example, in patent CN109378524A, by controlling the amount of FEC added, the gas production can be effectively suppressed and the high-temperature cycle capacity retention rate can be improved, but the impact on the impedance during the cycle is not mentioned. In patent CN117013082A, the combination of the first lithium salt (LiPF6), the second lithium salt (LiFSI), the positive electrode protection additive and the lithium salt additive can effectively improve the high-temperature cycle and high-temperature storage performance of lithium-ion batteries, while meeting the high-rate charge and discharge characteristics of the battery, but there is no specific description on improving the impedance growth, nor does it solve the problem of battery impedance growth; therefore, for the existing lithium-ion battery with FEC electrolyte, although the battery cycle performance can be improved, there are still problems of high temperature storage gas production and high battery impedance. Summary of the invention
[0004] In response to the above problems, the present application provides a non-aqueous electrolyte and a lithium battery, which can improve the cycle performance of the lithium-ion battery, reduce the battery impedance, inhibit the expansion and gas production of the lithium-ion battery in a high temperature environment, and take into account the battery fast charging requirements.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a non-aqueous electrolyte, comprising a lithium salt, an organic solvent and an additive, wherein the additive comprises a first additive and a carbonate compound, the carbonate additive comprises fluoroethylene carbonate, the first additive comprises a compound represented by structural formula 1, the lithium salt comprises lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, The non-aqueous electrolyte satisfies the relation 1; 5.2<a / (b+c)<20.7, relation 1; Wherein, a is the mass percentage of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide in the non-aqueous electrolyte, unit: %; b is the mass percentage of the fluoroethylene carbonate in the non-aqueous electrolyte, unit: %; c is the mass percentage of the first additive in the non-aqueous electrolyte, in %.
[0006] Preferably, the non-aqueous electrolyte satisfies Relationship 2: 5.66<a / (b+c)<12, Relationship 2.
[0007] Preferably, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage c of the first additive is 0.2%-0.5%.
[0008] Preferably, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content b of the fluoroethylene carbonate is 0.5% to 2%.
[0009] Preferably, c:b is 1:(1.6~7).
[0010] Preferably, c:b is 1:(2~5).
[0011] Preferably, based on the total mass of the non-aqueous electrolyte being 100%, the total mass percentage a of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide is 11-16%; In the lithium salt, the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is 1:(2-4.25).
[0012] Preferably, based on the total mass of the non-aqueous electrolyte being 100%, the total mass percentage a of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide is 12.5-15%; In the lithium salt, the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is 1:(2.1-3.7).
[0013] Preferably, the additive further comprises an auxiliary additive, and the auxiliary additive comprises one or more of cyclic sulfate additives, sulfonate additives, phosphate additives, borate additives, nitrile additives and ionic liquid additives; The lithium salts also include LiBF4, LiAsF6, LiClO4, LiBOB, LiDFOB, LiTFSI, LiPO2F2, LiCH3SO3, LiSbF6, LiCF3SO3, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiCl, LiBr, LiI, LiB10 Cl 10 , LiAlCl4, lithium chloroborane, lithium bis(fluorobis(oxalato)phosphate, lithium lower aliphatic carboxylate having 4 or less carbon atoms, lithium tetraphenylborate and lithium imide; Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the auxiliary additive is 0.01-15%; The organic solvent includes one or more of the non-aqueous organic solvent, including carbonate solvents, carboxylate solvents, sulfone solvents, ether solvents and nitrile solvents; Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the organic solvent is 5% to 80%.
[0014] On the other hand, the present application provides a lithium battery, comprising the non-aqueous electrolyte described above.
[0015] In the non-aqueous electrolyte provided by the present application, the added amounts of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), fluoroethylene carbonate and the first additive satisfy the relationship 5.2<a / (b+c)<20.7, lithium hexafluorophosphate and lithium bis(fluorosulfonyl imide) cooperate with each other to inhibit gas production during high-temperature storage of the battery; fluoroethylene carbonate and lithium bis(fluorosulfonyl imide) cooperate with each other, and the inorganic and organic cooperate with each other to inhibit the dissolution of lithium hexafluorophosphate, effectively improve the electrode interface stability, and increase the battery capacity retention rate; fluoroethylene carbonate and the first additive cooperate with each other to help form a low-impedance, stable structure, and complete SEI film at the negative electrode interface, reduce the decomposition and gas production of FEC, stabilize the positive electrode interface, reduce the interface impedance, improve the battery cycle performance, reduce the battery impedance growth, inhibit the gas production of the battery during high-temperature storage, and take into account the battery fast charging requirements. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] The present invention provides a non-aqueous electrolyte, including a lithium salt, an organic solvent and an additive, wherein the additive includes a first additive and a carbonate compound, the carbonate additive includes fluoroethylene carbonate, the first additive includes a compound shown in structural formula 1, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, The non-aqueous electrolyte satisfies the relation 1; 5.2<a / (b+c)<20.7, relation 1; Wherein, a is the mass percentage of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide in the non-aqueous electrolyte, unit: %; b is the mass percentage of the fluoroethylene carbonate in the non-aqueous electrolyte, unit: %; c is the mass percentage of the first additive in the non-aqueous electrolyte, in %.
[0018] The non-aqueous electrolyte provided by the present application, lithium hexafluorophosphate and lithium bis(fluorosulfonyl imide) work together to help improve the fast charging performance and battery cycle performance of the battery, and inhibit the gas production of the battery during high-temperature storage; the added first additive and fluoroethylene carbonate (FEC) work together to reduce the decomposition of FEC to produce HF, reduce the high-temperature gas production of the battery, stabilize the positive electrode interface, reduce the battery impedance, and improve the battery cycle performance; the added amounts of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), fluoroethylene carbonate and the first additive satisfy the relationship 5.2<a / (b+c)<20.7, lithium hexafluorophosphate and bis(fluorosulfonyl imide) Lithium fluorosulfonyl imide works together to inhibit gas production during high-temperature storage of the battery; fluoroethylene carbonate and lithium bis(fluorosulfonyl imide) work together, and the inorganic and organic cooperate with each other to inhibit the dissolution of lithium hexafluorophosphate, effectively improve the stability of the electrode interface, and increase the battery capacity retention rate; fluoroethylene carbonate and the first additive work together to help form a low-impedance, stable structure, and complete SEI film at the negative electrode interface, reduce the decomposition and gas production of FEC, stabilize the positive electrode interface, reduce the interface impedance, improve the battery cycle performance, reduce the battery impedance growth, inhibit the gas production of the battery during high-temperature storage, and take into account the battery fast charging needs.
[0019] If the value of the relationship a / (b+c) is less than 5.2, the relative contents of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are small, the conductivity of the electrolyte is reduced, the low-temperature performance of the battery is poor, the high-temperature cycle capacity retention rate is low, and the improvement in inhibiting gas production during high-temperature storage is not obvious; if the value of the relationship a / (b+c) is greater than 20.7, the high-temperature storage performance of the battery is poor, the inhibition of gas production during high-temperature storage is not obvious, and the battery impedance growth rate is high.
[0020] Specifically, the value of a / (b+c) can be 5.2, 6.0, 7.0, 8.0, 10.0, 12, 15, 17, 20, 20.7, etc., as long as the relationship 5.2<a / (b+c)<20.7 is satisfied.
[0021] In some preferred embodiments, the non-aqueous electrolyte satisfies Relationship 2: 5.66<a / (b+c)<12, Relationship 2.
[0022] Specifically, the non-aqueous electrolyte satisfies the relationship 2: 5.66<a / (b+c)<12, the battery has a higher high-temperature cycle capacity retention rate, lower battery impedance, and less gas production during high-temperature storage of the battery.
[0023] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage c of the first additive is 0.2% to 0.5%.
[0024] Specifically, adding the first additive in a mass content range of 0.2% to 0.5% into the electrolyte helps the first additive to cooperate with fluoroethylene carbonate, reduce HF produced by FEC decomposition, reduce high-temperature gas production of the battery, stabilize the positive electrode interface, reduce battery impedance, and improve battery cycle performance.
[0025] Specifically, the mass content of the first additive is in the range of 0.2% to 0.3%, 0.3% to 0.4% or 0.4% to 0.5%.
[0026] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content b of the fluoroethylene carbonate is 0.5% to 2%.
[0027] Specifically, 0.5% to 2% by mass of fluoroethylene carbonate (FEC) is added to the non-aqueous electrolyte. The LiF formed during the battery charging and discharging process cooperates with the anions in LiFSI, and the inorganic phase and the organic phase cooperate with each other, effectively inhibiting the dissolution of lithium salts, effectively improving the stability of the electrode interface, and improving the battery's capacity retention rate and cycle performance. As a negative electrode film-forming additive, fluoroethylene carbonate can form a low-impedance, structurally stable SEI film at the negative electrode interface, effectively reducing the interface impedance of the electrode, reducing the risk of lithium plating at the negative electrode under fast-charging conditions, and reducing solvent decomposition and gas production.
[0028] In the electrolyte, FEC decomposes to produce HF. Acidic substances such as HF will attack the positive electrode interface, causing the dissolution of transition metal ions in the positive electrode material. The first additive added to the electrolyte is a high-potential film-forming additive that can reduce the HF produced by the decomposition of FEC. The first additive and FEC work together to stabilize the positive electrode interface, reduce impedance, and improve battery cycle performance.
[0029] The mass content of fluoroethylene carbonate added to the non-aqueous electrolyte may be in the following ranges: 0.5% to 0.8%, 0.8% to 1.0%, 1.0% to 1.5% or 1.5% to 2.0%.
[0030] In some embodiments, c:b is 1:(1.6~7).
[0031] In the electrolyte, the mass ratio of the first additive added to FEC is 1: (1.6~7). The first additive can cooperate with fluoroethylene carbonate to reduce the decomposition of FEC to produce HF, reduce the high-temperature gas production of the battery, stabilize the positive electrode interface, reduce the battery impedance, and improve the battery cycle performance. If the mass ratio of the first additive to FEC is greater than 1:1.6, the amount of FEC added is small, the battery interface impedance increases, the solvent decomposition gas production increases, and the high-temperature storage gas production of the battery increases. If the mass ratio of the first additive to FEC is less than 1:7, the content of the first additive is small, the effect of the first additive in stabilizing the interface is not good, and the HF produced by the decomposition of FEC cannot be effectively reduced, and the impedance reduction effect is not obvious.
[0032] Specifically, the ratio of c:b can be in the following ranges, 1:(1.6~2.0), 1:(2.0~3.0), 1:(3.0~4.0), 1:(4.0~5.0), 1:(5.0~6.0) or 1:(6.0~7.0).
[0033] In some embodiments, c:b is 1:(2-5).
[0034] Specifically, the mass ratio of the first additive to FEC is in the range of 1:(2~5), which is more conducive to the synergy between the first additive and FEC, reducing the decomposition of FEC to produce HF, reducing battery gas production, reducing battery impedance, and improving battery cycle performance.
[0035] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the total mass percentage a of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide is 11-16%.
[0036] Specifically, the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the total mass percentage a of lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide is 11-16%. Lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate cooperate with each other, which helps to form a structurally stable SEI film at the negative electrode interface, inhibit the gas production of the battery during high-temperature storage, and improve the cycle performance of the battery; fluoroethylene carbonate and lithium bis(fluorosulfonyl)imide cooperate with each other, and inorganic and organic cooperate with each other to inhibit the dissolution of lithium hexafluorophosphate, effectively improve the stability of the electrode interface, and improve the battery capacity retention rate. Specifically, the total mass percentage a of lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide can be 11%, 11.5%, 12%, 12.4%, 13%, 14%, 15%, 16%, etc., as long as a is within the range of 11-16%.
[0037] In some preferred embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the total mass percentage a of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide is 12.5-15%.
[0038] Specifically, a is in the range of 12.5 to 15%, which helps lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate to cooperate with each other to form a complete and structurally stable SEI film at the negative electrode interface, inhibit gas production during high-temperature storage of the battery, and improve the cycle performance of the battery.
[0039] In some embodiments, in the lithium salt, the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is 1:(2-4.25).
[0040] The lithium salt lithium hexafluorophosphate (LiPF6) added to the traditional non-aqueous electrolyte has poor thermal stability and is easy to hydrolyze, which can easily cause rapid capacity decay in the battery and has limited application in high temperature and high pressure fields. The new lithium salt lithium bis(fluorosulfonyl)imide (LiFSI) has different anions from lithium hexafluorophosphate. Compared with lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide has a larger ion radius and higher dissociation ability, which can improve the ionic conductivity of the non-aqueous electrolyte and the charge and discharge performance of the battery, achieve fast charging and discharging, and help form an excellent SEI film to improve the high and low temperature performance of the battery. However, a high content of LiFSI also brings the risk of corroding the aluminum foil and reducing the high temperature performance and cycle performance of the battery. Lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are added to the non-aqueous electrolyte at the same time, and the mass ratio of the added lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is in the range of 1:(2~4.25). The content of the added lithium bis(fluorosulfonyl)imide is relatively small, which greatly reduces the risk of corrosion of the aluminum foil, improves the battery cycle performance, inhibits the gas production of the battery during high-temperature storage, and improves the battery fast charging performance.
[0041] Specifically, the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is 1:2, 1:2.3, 1:2.5, 1:2.8, 1:3.0, 1:3.5, 1:3.8, 1:4.0 or 1:4.25, as long as the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is within the range of 1:(2~4.25).
[0042] If the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is less than 1:2, the content of lithium bis(fluorosulfonyl)imide is too small, and the cycle performance of the battery is not significantly improved; if the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is greater than 1:4.25, the content of lithium bis(fluorosulfonyl)imide is too high, the risk of corrosion of the aluminum foil of the battery increases, and the high-temperature storage is degraded and gas is generated.
[0043] In some preferred embodiments, in the lithium salt, the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is 1:(2.1-3.7).
[0044] Specifically, the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate is in the range of 1:(2.1~3.7). The added lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate can synergistically form an excellent and stable SEI film at the negative electrode interface, improve the battery cycle performance, inhibit the high-temperature gas production of the battery, and improve the battery rate fast charging performance.
[0045] In some embodiments, the lithium salt further comprises LiBF4, LiAsF6, LiClO4, LiBOB, LiDFOB, LiTFSI, LiPO2F2, LiCH3SO3, LiSbF6, LiCF3SO3, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiCl, LiBr, LiI, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, lithium bis(fluorobis(oxalato)phosphate, lithium lower aliphatic carboxylate having 4 or less carbon atoms, lithium tetraphenylborate and lithium imide.
[0046] Specifically, the non-aqueous electrolyte provided in the present application includes, in addition to lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, the above-mentioned types of lithium salts, which can be added according to needs.
[0047] Lithium salt is a lithium ion transport medium in non-aqueous electrolyte. It provides and receives lithium ions during the battery charging and discharging process, which helps to improve the lithium ion conductivity. During the first charge and discharge process of the battery, the decomposition of lithium salt helps to form a SEI film at the negative electrode interface.
[0048] In some embodiments, in the non-aqueous electrolyte, the mass percentage of the lithium salt is 13-14.5%.
[0049] In some embodiments, the carbonate additive further comprises vinylene carbonate (VC), vinyl ethylene carbonate, or at least one of the compounds shown in Structural Formula 2: Structural formula 2 In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.
[0050] In some embodiments, the additive further includes an auxiliary additive, and the auxiliary additive includes one or more of a cyclic sulfate additive, a sulfonate additive, a phosphate additive, a borate additive, a nitrile additive, and an ionic liquid additive.
[0051] In some embodiments, the cyclic sulfate ester additive includes vinyl sulfate, propylene sulfate, methyl vinyl sulfate, At least one of; The sultone compound is selected from at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propylene sultone and methylene disulfonate; The borate additive is selected from tris(triethylsilane)borate; The phosphate compound is selected from at least one of tris(trimethylsilyl)phosphite or the compound shown in structural formula 3: Structural formula 3 In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; The borate compound is selected from tris(triethylsilane)borate; In a preferred embodiment, the unsaturated phosphate additive may be at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate; The nitrile additive is selected from at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0052] In other embodiments, the additives may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.
[0053] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the auxiliary additive is 0.01-15%.
[0054] It should be noted that, unless otherwise specified, in general, the amount of any one of the optional substances in the additives added to the non-aqueous electrolyte is less than 10%, preferably, the amount added is 0.1-5%, and more preferably, the amount added is 0.1%~2%. Specifically, the amount of any one of the optional substances in the additives can be 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%.
[0055] In some embodiments, the organic solvent includes the non-aqueous organic solvent including one or more of a carbonate solvent, a carboxylate solvent, a sulfone solvent, an ether solvent, and a nitrile solvent; Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the organic solvent is 5% to 80%.
[0056] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether having 3 to 10 carbon atoms and a cyclic ether having 3 to 6 carbon atoms. The cyclic ether may be, but is not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but is not limited to, at least one of dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, diethylene glycol dimethyl ether, 1,3-dioxolane, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ion conductivity, are particularly preferred. Ether solvents can be used alone or in any combination and ratio. There is no special restriction on the amount of ether solvent added, which is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. In the non-aqueous solvent volume ratio of 100%, the volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less. When two or more ether solvents are used in combination, the total amount of the ether solvents can meet the above range. When the amount of ether solvent added is within the above preferred range, it is easy to ensure the improvement of ion conductivity brought about by the increase in lithium ion dissociation of the chain ether and the reduction in viscosity. Furthermore, when the negative electrode active material is a carbon material, the co-intercalation phenomenon of the chain ether and lithium ions can be suppressed, so that the input-output characteristics and the charge-discharge rate characteristics can be brought into appropriate ranges.
[0057] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.
[0058] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate. The cyclic carbonate may be, but is not limited to, at least one of vinylene carbonate, ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), butylene carbonate (BC), and butylene carbonate; the chain carbonate may be, but is not limited to, at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC).
[0059] The content of cyclic carbonate is not particularly limited, and is arbitrary within the scope of not significantly destroying the effect of the lithium ion battery of the present invention, but the lower limit of its content in the case of using one alone is relative to the total amount of solvent of nonaqueous electrolyte, usually 3% or more, preferably 5% or more by volume. By setting this scope, it is possible to avoid the reduction of conductivity due to the reduction of the dielectric constant of nonaqueous electrolyte, and it is easy to make the large current discharge characteristics of nonaqueous electrolyte battery, the stability relative to the negative pole, and the cycle characteristics reach a good range. In addition, the upper limit is usually 90% or less by volume, preferably 85% or less by volume, and more preferably 80% or less by volume. By setting this scope, the oxidation / reduction tolerance of nonaqueous electrolyte can be improved, thereby contributing to the stability during high temperature storage. The content of chain carbonate is not particularly limited, and relative to the total amount of solvent of nonaqueous electrolyte, it is usually 15% or more by volume, preferably 20% or more by volume, and more preferably 25% or more by volume. In addition, usually 90% or less by volume, preferably 85% or less by volume, and more preferably 80% or less by volume. By making the content of linear carbonate in above-mentioned scope, easily make the viscosity of nonaqueous electrolytic solution reach appropriate range, suppress the reduction of ionic conductivity, and then contribute to make the output characteristics of nonaqueous electrolyte battery reach good scope.When using two or more linear carbonates in combination, make the total amount of linear carbonate satisfy above-mentioned scope.
[0060] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.
[0061] The carboxylate solvent includes cyclic carboxylate and / or chain carboxylate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carboxylate include at least one of methyl formate, methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), butyl propionate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethyl acetate, and ethyl trimethyl acetate.
[0062] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. There is no special restriction on the amount of sulfone solvent added, and it is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent of the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of sulfone solvents can be made to meet the above range. When the amount of sulfone solvent added is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.
[0063] In a preferred embodiment, the solvent is a mixture of cyclic carbonate and linear carbonate.
[0064] On the other hand, the present application provides a lithium battery, comprising the non-aqueous electrolyte described above.
[0065] The lithium battery provided in the present application uses the non-aqueous electrolyte described above, satisfies the relationship 5.2<a / (b+c)<20.7, lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide cooperate with each other to inhibit the gas production of the battery during high-temperature storage; fluoroethylene carbonate and lithium bis(fluorosulfonyl)imide cooperate with each other to inhibit the dissolution of lithium hexafluorophosphate, effectively improve the electrode interface stability, and improve the battery capacity retention rate; fluoroethylene carbonate and the first additive cooperate with each other to help form a low-impedance, stable structure, and complete SEI film at the negative electrode interface, reduce the decomposition and gas production of FEC, stabilize the positive electrode interface, reduce the interface impedance, improve the battery cycle performance, reduce the battery impedance, and reduce the gas production during high-temperature storage.
[0066] In some embodiments, the positive electrode includes a positive electrode material layer, and the positive electrode material layer is obtained by mixing a positive electrode active material, a positive electrode conductor, and a positive electrode binder.
[0067] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and a ternary material.
[0068] Furthermore, the positive electrode active material includes LiNi x Co y Mn z L (1-x-y-z) O2、LiCo x' L (1-x´) O2、LiNi x'' L' y' Mn (2-x''-y') O4、Li z'At least one of MPO4, wherein L is at least one of Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, or Fe, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < x + y + z ≤ 1, 0 < x' ≤ 1, 0.3 ≤ x'' ≤ 0.6, 0.01 ≤ y' ≤ 0.2, L' is at least one of Co, Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, Fe; 0.5 ≤ z' ≤ 1, and M is at least one of Fe, Mn, Co.
[0069] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon spheres, conductive graphite, SP, carbon fiber, carbon nanotubes, graphene, or reduced graphene oxide. Preferred are carbon nanotubes, SP, and conductive graphite.
[0070] The positive electrode binder includes at least one of polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride - hexafluoropropylene, copolymers of tetrafluoroethylene - hexafluoropropylene, copolymers of tetrafluoroethylene - perfluoroalkyl vinyl ether, copolymers of ethylene - tetrafluoroethylene, copolymers of vinylidene fluoride - tetrafluoroethylene, copolymers of vinylidene fluoride - trifluoroethylene, copolymers of vinylidene fluoride - trichloroethylene, copolymers of vinylidene fluoride - fluoroethylene, copolymers of vinylidene fluoride - hexafluoropropylene - tetrafluoroethylene, thermoplastic polyimides, thermoplastic resins such as polyethylene and polypropylene; acrylic resins; sodium carboxymethyl cellulose; polyvinyl butyral; ethylene - vinyl acetate copolymer; polyvinyl alcohol; and styrene - butadiene rubber.
[0071] In some embodiments, the positive electrode further includes a positive electrode current collector, and the positive electrode material layer is formed on the surface of the positive electrode current collector.
[0072] The positive electrode current collector is selected from metal materials that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0073] In some embodiments, the lithium battery further includes a negative electrode. The negative electrode includes a negative electrode material layer, and the negative electrode material layer includes a negative electrode active material. The negative electrode active material is selected from at least one of carbon materials, carbon - silicon composites, silicon - based negative electrodes, lithium - based negative electrodes, and tin - based negative electrodes.
[0074] In a preferred embodiment, the carbon material may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.
[0075] The silicon-based negative electrode includes at least one of silicon material, silicon oxide, silicon-carbon composite material and silicon alloy material; the lithium-based negative electrode includes at least one of metal lithium or lithium alloy. The lithium alloy can be at least one of lithium silicon alloy, lithium sodium alloy, lithium potassium alloy, lithium aluminum alloy, lithium tin alloy and lithium indium alloy. The tin-based negative electrode includes at least one of tin, tin carbon, tin oxygen and tin metal compound.
[0076] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.
[0077] The selectable ranges of the negative electrode binder and the negative electrode conductor are the same as those of the positive electrode binder and the positive electrode conductor, respectively, and will not be described in detail here.
[0078] In some embodiments, the negative electrode sheet further includes a negative electrode current collector, and the negative electrode material layer is formed on a surface of the negative electrode current collector.
[0079] The negative electrode current collector is selected from metal materials that can conduct electrons. Preferably, the negative electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the negative electrode current collector is selected from copper foil.
[0080] In some embodiments, the diaphragm includes a substrate layer and a surface coating disposed on at least one side of the substrate layer, and the substrate layer includes but is not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP, etc.
[0081] The present invention is further described below by way of examples.
[0082] Example 1 This embodiment is used to illustrate a non-aqueous electrolyte and a lithium battery disclosed in the present invention.
[0083] 1) Preparation of positive electrode The positive electrode active material ternary nickel-cobalt-manganese, conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:3:2 and dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on both sides of the aluminum foil, and then dried, rolled and vacuum dried. After the aluminum lead wire is welded with an ultrasonic welder, a positive electrode plate is obtained. The thickness of the plate is between 120-150μm. The compaction density of the positive electrode material is controlled by the surface density and rolling thickness of the positive electrode material. The compaction density of the positive electrode is 3.0g / cm 3 -4.4g / cm 3 between.
[0084] 2) Preparation of negative electrode Artificial graphite, conductive carbon black, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94.7:1.5:2.4:1.4 and dispersed in deionized water to obtain a negative electrode slurry. The negative electrode slurry is coated on the surface of the conductive carbon layer, and then dried, calendered and vacuum dried, and a nickel lead wire is welded with an ultrasonic welder to obtain a negative electrode plate.
[0085] 3) Preparation of non-aqueous electrolyte In a glove box (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), propylene carbonate PC, diethyl carbonate (DEC), and propyl propionate (PP) are mixed uniformly in a mass ratio of 20:10:10:60, and lithium salt and additives are added and mixed uniformly to obtain a non-aqueous electrolyte. The lithium salts are lithium hexafluorophosphate and lithium bisfluorosulfonyl imide, and the mass contents of lithium hexafluorophosphate and lithium bisfluorosulfonyl imide in the electrolyte are shown in Table 1; the additives include FEC and a first additive, and in the non-aqueous electrolyte, the mass percentage content of FEC is b, and the mass percentage content of the first additive is c, and the specific values are shown in Table 1.
[0086] 4) Preparation of lithium-ion batteries A polypropylene separator is placed between the positive and negative electrodes, and then the sandwich structure consisting of the positive, negative and separator is wound, and then the wound body is flattened and placed in a square aluminum metal shell, and the lead wires of the positive and negative electrodes are welded to the corresponding positions of the cover plate, and the cover plate and the metal shell are welded together with a laser welding machine, and vacuum baked at 75°C for more than 48 hours to obtain a battery cell to be injected with liquid. Then, the injection and formation processes are carried out to prepare the lithium-ion battery cell.
[0087] Examples 2-27 and Comparative Examples 1-9 Examples 2-27 and Comparative Examples 1-8 are used to illustrate the non-aqueous electrolyte and battery disclosed in the present invention, including most of the operating steps in Example 1, and the difference is that the mass percentage of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide added to the electrolyte, the mass percentage of FEC b, and the mass percentage of the first additive c are different, and the specific values are shown in Table 1; the types and contents of the auxiliary additives are different, see Table 1 for details.
[0088] Comparative Example 9 is similar to Example 1 in most of the steps, except that the lithium salt in Comparative Example 9 is lithium hexafluorophosphate and lithium tetrafluoroborate, without lithium bis(fluorosulfonyl)imide; and the mass percentage of lithium tetrafluoroborate in the electrolyte is 1%.
[0089] Most of the steps of Examples 26-27 are the same as those of Example 1, except that in addition to the additives listed in Table 1, auxiliary additives are added to Examples 26-27. The auxiliary additive added to Example 26 is tris(trimethylsilyl)phosphate (TMSP), and the auxiliary additive added to Example 27 is 1,3-propanesultone (PS). In the electrolyte of Example 26, the mass content of TMSP is 0.5%; in the electrolyte of Example 27, the mass content of PS is 0.5%.
[0090] Most of the steps of Comparative Examples 7 and 8 are the same as those of Example 1, except that in addition to the additives listed in Table 1, an auxiliary additive is added to Comparative Examples 7 and 8, and the auxiliary additive added to Comparative Examples 7 and 8 is tris(trimethylsilyl) phosphate (TMSP). In the electrolytes of Comparative Examples 7 and 8, the mass content of PS is 0.5%.
[0091] Table 1 Electrolyte parameters of Examples 1-27 and Comparative Examples 1-9 Performance Testing The lithium ion batteries prepared in the above Examples 1-27 and Comparative Examples 1-9 were subjected to the following performance tests.
[0092] 25℃ normal temperature cycle test: At 25°C, charge the battery to 4.4V with 0.5C constant current and constant voltage, and cut off current 0.05C; then discharge to 3.0V with 0.5C constant current, and pre-cycle 2 cycles. Then, place at 25°C for 3 hours, charge to 4.4V with 3C constant current and constant voltage, and discharge with 3C constant current, record the discharge capacity and impedance of the first cycle, and then cycle at 3C / 3C in the voltage range of 3-4.4V. The calculation formula is as follows: The 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / 1st cycle discharge capacity) × 100%.
[0093] The growth rate of the 500th cycle impedance (%) = (500th cycle impedance - 1st cycle impedance) / 1st cycle impedance × 100%.
[0094] Battery 60℃ high temperature storage performance At 25°C, charge the battery to 4.4V with 0.5C constant current and constant voltage, cut-off current 0.05C, discharge to 3.0V with 1C constant current, record the initial capacity C1 of the battery, then charge to 4.4V with 0.5C constant current and constant voltage, cut-off current 0.05C, fully charge, measure the volume with drainage method, record the initial volume V1. Then, after storing in a 60°C environment for 7 days, test the volume V2 after storage, then discharge to 3.0V with 1C, test the battery retention capacity C2.
[0095] Capacity retention rate = C2 / C1×100% Volume expansion rate = (V2-V1) / V1×100% The test data is shown in Table 2.
[0096] Table 2 Performance data table of Examples 1-27 and Comparative Examples 1-9.
[0097] It can be seen from Tables 1 and 2 that, in comparison between Example 1 and Comparative Examples 1-6, there is no lithium hexafluorophosphate in Comparative Example 2, and the electrical performance of the battery is poor. In Comparative Example 1, lithium hexafluorophosphate is added, but lithium bis(fluorosulfonyl)imide is not added, and the gas production of the battery is serious, and the cycle performance and high-temperature storage performance are poor. In Comparative Example 3, there is no fluoroethylene carbonate, and although the gas production of the battery is reduced, the high-temperature storage performance of the battery is poor. In Comparative Example 4, the battery impedance growth rate is high without the first additive. In Comparative Examples 5 and 6, although lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate and the first additive are added to the electrolyte, the relationship of 5.2<a / (b+c)<20.7 is not satisfied, and the high-temperature storage performance and cycle performance of the battery depend on the above. However, it is relatively poor; it means that the electrolyte satisfies the relationship 5.2<a / (b+c)<20.7, lithium hexafluorophosphate and lithium bis(fluorosulfonyl imide) work together to inhibit the gas production of the battery during high-temperature storage; fluoroethylene carbonate and lithium bis(fluorosulfonyl imide) work together, and the inorganic and organic cooperate with each other to inhibit the dissolution of lithium hexafluorophosphate, effectively improve the electrode interface stability, and increase the battery capacity retention rate; fluoroethylene carbonate and the first additive work together to help form a low-impedance, stable structure, and complete SEI film at the negative electrode interface, reduce the decomposition and gas production of FEC, stabilize the positive electrode interface, reduce the interface impedance, improve the battery cycle performance, reduce the battery impedance growth, inhibit the gas production of the battery during high-temperature storage, and take into account the battery fast charging needs.
[0098] Comparing Example 1 with Comparative Example 9, the lithium salt in Comparative Example 9 is lithium hexafluorophosphate and lithium tetrafluoroborate, the battery produces more gas, the high-temperature storage capacity retention rate is low, the cycle capacity retention rate is low, and the impedance growth rate is high, indicating that lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide have mutual synergy, improve the battery cycle performance, and inhibit the gas production of the battery during high-temperature storage.
[0099] Comparing Example 1 with Examples 20-25, in Example 20-21, a is lower than 11%, and it is speculated that the electrolyte conductivity is low, and the room temperature cycle capacity retention rate of the battery is low; a is higher than 16%, and gas production is serious; in Example 22-23, b is lower than 0.5%, the high temperature storage and cycle capacity retention rates of the battery are too low, and the cycle impedance growth rate is high; b is higher than 2%, the battery cycle impedance growth rate is high, and the high temperature storage capacity retention rate is too low; in Example 24-25, c is not in the range of 0.2%~0.5%, the content of the first additive is too low or too high, the battery produces gas, and the cycle impedance growth rate is too high; it indicates that the electrolyte satisfies the relationship 5.2<a / (b+c)<20.7, and a is in the range of 11~16%, c is 0.2%~0.5%, and b is in the range of 0.5%~2%, the high temperature storage capacity retention rate of the battery is high, gas production is low, the cycle capacity retention rate is high, and the cycle impedance growth rate is low.
[0100] Comparison between Examples 1-5 and 6-7 shows that the mass content of lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate is in the range of 11-16%, and the mass ratio is in the range of 1:(2-4.25), the battery has a high cycle capacity retention rate and a low impedance growth rate. Comparison between Examples 1, 10-13 and 14-15 shows that c is 0.2%-0.5%, b is 0.5%-2%, and c:b is 1:(1.6-7), the battery has a low cycle impedance growth rate and low gas production, indicating that the first additive can cooperate with fluoroethylene carbonate to reduce the decomposition of FEC to produce HF, reduce high-temperature gas production of the battery, stabilize the positive electrode interface, reduce the battery impedance, and improve the battery cycle performance.
[0101] Compared with Examples 1-21, the electrolyte satisfies the relationship 5.66<a / (b+c)<12, the battery has lower cycle impedance, higher cycle capacity retention rate, less gas production, and high high-temperature storage capacity retention rate.
[0102] Comparing Example 26 with Comparative Examples 7-8, there is no FEC in Comparative Example 7 and no first additive in Comparative Example 8. The high-temperature storage performance and cycle performance of the battery are poor, and the impedance is high. For Example 1 and Examples 26-27, when the electrolyte satisfies the relationship 5.2<a / (b+c)<20.7 and an auxiliary additive is added, the auxiliary additive can cooperate with the first additive and FEC to further improve the battery's cycle capacity retention rate and high-temperature storage capacity retention rate, reduce gas production, and reduce the battery cycle impedance growth rate.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A non-aqueous electrolyte, characterized in that: The invention comprises a lithium salt, an organic solvent and an additive, wherein the additive comprises a first additive and a carbonate compound, the carbonate additive comprises fluoroethylene carbonate, the first additive comprises a compound shown in structural formula 1, and the lithium salt comprises lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. The non-aqueous electrolyte satisfies the relation 1; 5.2<a / (b+c)<20.7, relation 1; Wherein, a is the mass percentage of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide in the non-aqueous electrolyte, unit: %; b is the mass percentage of the fluoroethylene carbonate in the non-aqueous electrolyte, unit: %; c is the mass percentage of the first additive in the non-aqueous electrolyte, in %.
2. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte satisfies Relationship 2: 5.66<a / (b+c)<12, Relationship 2.
3. The non-aqueous electrolyte according to claim 1 or 2, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage c of the first additive is 0.2% to 0.5%.
4. The non-aqueous electrolyte according to claim 3, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content b of the fluoroethylene carbonate is 0.5% to 2%.
5. The non-aqueous electrolyte according to claim 4, characterized in that c:b is 1:(1.6~7).
6. The non-aqueous electrolyte according to claim 5, characterized in that c:b is 1:(2~5).
7. The non-aqueous electrolyte according to claim 1, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the total mass percentage a of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide is 11-16%; In the lithium salt, the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is 1:(2-4.25).
8. The non-aqueous electrolyte according to claim 7, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the total mass percentage a of the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide is 12.5-15%; In the lithium salt, the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is 1:(2.1-3.7).
9. The non-aqueous electrolyte according to claim 1, characterized in that The additives further include auxiliary additives, and the auxiliary additives include one or more of cyclic sulfate additives, sulfonate additives, phosphate additives, borate additives, nitrile additives and ionic liquid additives; The lithium salts also include LiBF4, LiAsF6, LiClO4, LiBOB, LiDFOB, LiTFSI, LiPO2F2, LiCH3SO3, LiSbF6, LiCF3SO3, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiCl, LiBr, LiI, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, lithium bis(fluorobis(oxalato)phosphate, lithium lower aliphatic carboxylate having 4 or less carbon atoms, lithium tetraphenylborate and lithium imide; Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the auxiliary additive is 0.01-15%; The organic solvent includes one or more of the non-aqueous organic solvent, including carbonate solvents, carboxylate solvents, sulfone solvents, ether solvents and nitrile solvents; Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the organic solvent is 5% to 80%.
10. A lithium battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolyte capable of suppressing gas production of lithium ion batteries
CN109378524A
High-voltage-resistant electrolyte and lithium ion battery
CN117013082A
Cited By
Non-aqueous electrolyte and lithium ion battery
CN121215903A